Efficacy of Ethanol Extract of Papaya Leaves (Carica papaya var California L.) on Mortality of Instar III Larvae of Aedes aegypti Mosquito - Choirul Oktavian Setiyadin Nayiron; Hastutiek, Poedji; Dewa Ketut Meles; Eduardus Bimo Aksono Herupradoto; Mochamad Lazuardi; Agus Sunarso (Universitas Airlangga, 2025)
This study aims to evaluate the efficacy of Papaya var California leaves extract and identify its effective concentration in inducing mortality among third-instar larvae of Aedes aegypti mosquitoes. The study utilized adult Ae. aegypti mosquitoes as the experimental subjects. This study was an experimental study with a comparative Completely Randomized Design The test groups include negative control, 2.5 mg/mL, 5 mg/mL, 10 mg/mL and positive control. Each test used 20 third instar larvae of Ae.aegypti mosquitoes, with four repeats.. The test groups were 2.5 mg/mL, 5 mg/mL, 10 mg/mL, and the control groups were A negative control contained distilled water and Tween 20, and a positive control contained abate (temephos) Based on Kruskall-wallis test shows a significant difference. The results indicated that the optimal concentration was 10 mg/mL, with the highest effectiveness observed at the 30th time hours.